National Health Interview Survey, 1995: Year 2000 Objectives Supplement ([Verlag nicht ermittelbar], 1998)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. This supplement includes variables from the NHIS core Person File (see NATIONAL HEALTH INTERVIEW SURVEY, 1995 [ICPSR 2533]), including sex, age, race, marital status, veteran status, education, income, industry and occupation codes, and limits on activity. The Year 2000 Supplement contains items on five selected topics that relate to the Department of Health and Human Services (HHS) Year 2000 Health Objectives: tobacco, nutrition, clinical preventive services, mental health, and physical activity and fitness. Variables relating to smoking include respondent's current smoking status and tobacco use. Items on nutrition cover participation in activities to control weight, exercise, salt intake, and fat intake. Variables in the clinical preventive services section provide information on whether the respondent had a flu shot in the last year, a tetanus shot in the last 10 years, or the pneumonia vaccination, whether the respondent had diabetes, asthma, emphysema, chronic bronchitis, TB, or chronic kidney and liver disease in the past year, whether the respondent experienced extreme fatigue, and whether he or she was treated for cancer. The mental health section includes items on the levels of stress the respondent experienced, the effects of stress on health, steps taken to control stress, emotional/personal problems in the past year, and whether any treatment for these problems had been sought. Variables on physical activity and fitness include types of exercise (walking, gardening, stretching, weight- lifting, jogging, aerobics or aerobic dancing, bicycle riding, stair climbing, swimming, tennis, golf, baseball, handball/raquetball or squash, downhill skiing, cross-country skiing, water skiing, basketball, volleyball, soccer, football, and other sports), how often the respondent performed the activity, number of minutes spent doing the activity, and change in heart rate during the activity. Additionally, respondents were asked about the length of time since their last check-up and whether the doctor had recommended that exercise be started or continued.